Hydrogen peroxide‐dependent antibacterial action of Melilotus albus honey. (July 2017) - Sowa, P.; Grabek‐Lejko, D.; Wesołowska, M.; Swacha, S.; Dżugan, M.
Abstract: Honey originating from different floral sources exhibits the broad spectrum of antibacterial activity as a result of the presence of hydrogen peroxide as well as nonperoxide bioactive compounds. The mechanisms of antibacterial activity of Polish melilot honey were investigated for the first time. Polish melilot honey samples ( Melilotus albus biennial = 3 and annual = 5, Melilotus officinalis = 1) were collected directly from beekeepers and analysed for pollen profile, basic physicochemical parameters, antioxidant capacity, radical scavenging activity, total phenolic contents as well as antibacterial properties against pathogenic bacteria Staphylococcus aureus, Escherichia coli, Klebsiella pneumoniae, Salmonella spp. The physicochemical properties of melilot honey were specific for light‐coloured unifloral honey samples and were not dependent on its botanical and geographical origin ( P > 0·05). All tested honey samples exhibited inhibitory activity (above 90%) against Gram‐positive bacteria at the concentration of 12·5–25%. Above 30–50% of antibacterial activity of melilot honey was connected with glucose oxidase enzyme action and was destroyed in the presence of catalase. Hydrogen peroxide‐dependent antibacterial activity of honey was inversely correlated with its radical scavenging activity ( r = −0·67) and phenolic compounds ( r = −0·61). Antibacterial action of melilot honey depends not only on hydrogen peroxide produced by glucose oxidase, but also on other nonperoxide bioactive components of honey. Significance and Impact of the Study: Melilot honey is used in traditional medicine as an anticoagulant agent due to the possibility of the presence of the coumarin compounds which are specific for Melilotus plant. Melilotus albus is rarely used to produce honey, and antibacterial properties of this variety of honey had not been studied yet. Nine samples of melilot honey produced in different regions of Poland were analysed according to their antibacterial activity which was correlated with physiochemical parameters and antioxidant activity. It was shown that antibacterial activity of melilot honey is created by hydrogen peroxide and other bioactive compounds. Abstract : Significance and Impact of the Study: Melilot honey is used in traditional medicine as an anticoagulant agent due to the possibility of the presence of the coumarin compounds which are specific for Melilotus plant. Melilotus albus is rarely used to produce honey, and antibacterial properties of this variety of honey had not been studied yet. Nine samples of melilot honey produced in different regions of Poland were analysed according to their antibacterial activity which was correlated with physiochemical parameters and antioxidant activity. It was shown that antibacterial activity of melilot honey is created by hydrogen peroxide and other bioactive compounds.